Microscale Concert Hall Acoustics to Produce Uniform Ultrasound Stimulation for Targeted Sonogenetics in hsTRPA1‐Transfected Cells. Issue 5 (16th February 2022) - Vasan, Aditya; Allein, Florian; Duque, Marc; Magaram, Uri; Boechler, Nicholas; Chalasani, Sreekanth H.; Friend, James
Abstract : Ultrasound neuromodulation has rapidly developed over the past decade, a consequence of the discovery of strain‐sensitive structures in the membrane and organelles of cells extending into the brain, heart, and other organs. A key limitation to its use in the brain is the formation of standing waves within the skull. In standing acoustic waves, the maximum ultrasound intensity spatially varies from near zero to double the mean in one‐half of a wavelength, and has led to localized tissue damage and disruption of normal brain function while attempting to evoke a broader response. This phenomenon also produces a large spatial variation in the actual ultrasound exposure in tissue, leading to heterogeneous results. One approach to overcome this limitation is presented here: transducer‐mounted diffusers that result in spatiotemporally incoherent ultrasound. It is shown through experiment and analysis that adding a diffuser to the transducer leads to a twofold increase in ultrasound responsiveness of transient receptor potential ankyrin 1 (TRPA1)‐transfected human embryonic kidney cells. Furthermore, it is shown that the diffuser produces a uniform spatial distribution of pressure within the rodent skull. The approach offers uniform ultrasound delivery into irregular cavities for sonogenetics. Abstract : Positioning a microscale diffuser directly on an ultrasound transducer produces spatiotemporally uniform ultrasound within the skull cavity of a mouse, useful for sonogenetics; the actuation of targeted regions of the brain expressing candidate channels using ultrasound in conjunction with transfection of the target tissue to produce ultrasound‐sensitive TRPA1 ion channels.